Combined quality value investing - Kern, Levi Friedemann (2022)
This work project evaluates whether an investment strategy that combines the quality factor with the value factor yields superior risk-adjusted returns to quality as a stand-alone strategy. In this context, a unique quality factor based on profitability, earnings quality and safety is combined with value metrics and optimized over an in-sample period. The out-of-sample analysis shows that the combined strategy fails to outperform the quality-only strategy. The thesis also finds that constructing a three-dimensional quality factor enhances its risk-adjusted performance and confirms the existence of the quality premium.